From cooperation to globalization - UNGUREANU, Gabriela (Annals of Spiru Haret University. Economic Series, 2010)
Globalization is seen as a consequence of cross-border business. This complex and irreversible process can be seen as an extension of capitalist relations of production or increased interdependence in the economic system. Globalization has given rise to more and more fields of activity worldwide. To meet the challenges of business globalization, many companies form strategic alliances, cooperate or merge with other companies. Cooperation is seen by many companies as an alternative path to success. In recent years joint international associations, licensing, co-production agreements, joint research programs, exploration of consortia and other cooperative relationships between two or more corporations with potential have increased. We notice a cooperation tendency among small-sized companies, especially among those from the developing countries.